Tin-Powder-Promoted One-Pot Synthesis of 5-Trifluoromethyl-5-aryl-3-methylidenepyrrolidin-2-ones - Wang, Ke-Hu; Wang, Jianglong; Wang, Yalin; Su, Yingpeng; Huang, Danfeng; Fu, Ying; Du, Zhengyin; Hu, Yulai (Synthesis, 2018)
A simple and efficient synthetic approach is reported for the synthesis of 5-trifluoromethyl-5-aryl-3-methylidenepyrrolidin-2-ones in moderate to excellent yields via an acid-catalyzed one-pot multicomponent reaction of aromatic trifluoromethyl ketones, acylhydrazines, and ethyl 2-(bromomethyl)acrylate promoted by tin powder. The protocol is operationally simple. The overall process involves allylation and cyclization of the intermediate of acylhydrazones.
Keywords: lactams; allylation; tin; trifluoromethyl ketones; acylhydrazines